Strategi Customer Service Dalam Complaint Handling Pada Bank Syariah Indonesia KCP Rantauprapat - Khomisah Khomisah (Yayasan Rahmat Islamiyah, 2022)
This research is motivated by the existence of complaints or complaints submitted by customers of Bank Syariah Indonesia KCP Rantauprapat. This study aims to determine the customer service strategy in handling customer complaints, and to find out the factors that support and hinder the work process of customer service strategies at BSI KCP Rantauprapat. The type of research used is descriptive qualitative, namely research that is intended to provide accurate information related to the field. The source of this research data was taken through interviews with customer service at Bank Syariah Indonesia KCP Rantauprapat. Data collection techniques used are observation, interviews, and documentation. From the research conducted by the author, it can be stated that the customer service strategy used in handling customer complaints is to follow the Standard Operating Procedures (SOP) for existing services such as doing first greetings to customers at the beginning of service, then handling customer complaints by analyzing cases that occur quickly and accurately. appropriate, then provide an explanation regarding the process, costs and requirements required, as well as verifying the data attached by the customer to filling out the complaint application form. Then proceed with reconfirming and inputting data by customer service. Then do cross selling (conditional), and end service to customers. In carrying out the customer service strategy, there are several supporting and inhibiting factors. The supporting factors are the presence of employees who have experience in dealing with customer complaints, the existence of communication training for employees so that it is easier to communicate with customers and the existence of understanding from customers about the condition of the Bank. And the inhibiting factor is the lack of information from the Bank to customers.